Effect of an α-calcium sulfate hemihydrate/treated dentin matrix composite to regenerate bone in critically sized SD rat calvarial defects - Wang, Mengmeng; Li, Bingyan; Li, Wenshuai; Hu, Zelong; Fu, Haojie; Li, Rui (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction α-Calcium sulfate hemihydrate (α-CSH) is a widely used artificial bone graft material, but it suffers from rapid deterioration and limited osteoinductivity. This study aims to develop composite cements by combining treated dentin matrix (TDM) with α-CSH to enhance osteogenic properties for the healing of bone deformities. Methods The composite cements were prepared by mixing treated dentin matrix (TDM) with α-calcium sulfate hemihydrate (α-CSH) and characterized for their mechanical, morphological, and chemical properties using a universal mechanical testing machine, scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier-transform infrared (FTIR) spectroscopy. The biological performance was assessed by measuring osteoblast proliferation using the CCK-8 test and evaluating new bone formation in a calvarial bone defect model in rats. Results The compressive strength of the TDM/α-CSH cements decreased with increasing TDM mass ratio, while SEM analysis revealed a distinct three-dimensional porous network structure and increased surface roughness upon thorough mixing. XRD and FTIR studies confirmed the physical mixture of the two materials without phase changes. The TDM/α-CSH composites significantly stimulated osteoblast proliferation, which was dependent on the TDM content, and demonstrated superior enhancement in new bone formation as confirmed by X-ray examination and micro-CT analysis. Discussion The findings suggest that TDM/α-CSH composite cements have promising potential as an alternative for repairing bone defects due to their improved mechanical properties, osteoblast proliferation, and enhanced new bone formation in vivo. Conclusion TDM/α-CSH composite cements show potential as a novel bone graft material, offering advantages in terms of mechanical strength, osteoconductivity, and osteoinductivity, making them a viable option for bone repair applications.